SISTEM INFORMASI PELAYANAN KESEHATAN DI LABORATORIUM KLINIK PARANIDA BANDUNG - Deasy Permatasari; Fanji Wijaya (Sekolah Tinggi Teknik - PLN, 2015)
Clinical Laboratory Paranida a means of supporting health. Improving the Quality ofLaboratory Services through standardization of services that includes aspects of service procedures,inspection procedures and diagnostic accuracy you need for a healthier life. Found problems thatoccur in the processing of patient data, which is still done with the recording system and thecalculation process payment transactions are still not maximizing the computerized system so wellthat in making patient data reports and financial statements requires quite a long time.The method used is the system approach structured design. Where structured design is thedevelopment of a model of problem solving analysis results by using acomputer system that hascomponents - components and relationships are the same or similar to the original problem. Thedevelopment of the system used in this research is to create a prototype using an iterative method inthe model System Development Life Cycle (SDLC). The tool used to describe the system model is adata flow diagram (FlowMap), context diagrams, and data flow diagram (DFD), as well as indatabase design using a data dictionary, normalization, and Entity Relation Diagram (ERD). In thedesign of Health Care Information Systems is using the programming language supported byNetBeans IDE 6.9.1 with MySQL as the database.After passing through the stages of implementation and testing, the results obtained are betterdata storage and ease of administration are effective in preparing reports and archiving structuredreports. System information created is expected to assist the Clinical Laboratory Paranida inimproving health services and their performance.